Homoharringtonine Attenuates Dextran Sulfate Sodium-Induced Colitis by Inhibiting NF-κB Signaling - Jiangrui Liu; Liangpan Shi; Wenchang Huang; Zhihua Zheng; Xiaohui Huang; Yibin Su (Mediators of Inflammation)
Homoharringtonine (HHT) exhibits an anti-inflammatory activity. The potential protective effects and mechanisms of HHT on dextran sulfate sodium- (DSS-) induced colitis were investigated. DSS-induced colitis mice were intraperitoneally injected with HHT. Body weight, colon length, disease activity index (DAI), and histopathological change were examined. The relative contents of interleukin- (IL-) 1β, tumor necrosis factor- (TNF-) α, IL-6, and the chemokine (C-C motif) ligand 2 (CCL2) in the colon tissues and HHT-treated RAW264.7 cells were detected with the enzyme-linked immunosorbent assay. In the meantime, the levels of p-p65 and p-IκBα were detected by Western blot. The proportion of macrophages (CD11b+F4/80+) in the colon tissues was detected by flow cytometry. HHT alleviated DSS-induced colitis with downregulated TNF-α, IL-1β, IL-6, and CCL2 expression; reduced activation of nuclear factor-kappa B (NF-κB) signaling; and diminished proportion of recruited macrophages in colon tissues. It was further testified that HHT inhibited lipopolysaccharide-induced macrophage activation with reduced activation of NF-κB signaling. In addition, HHT inhibited the M1 polarization of both human and mouse macrophages, while HHT did not affect the differentiation of human CD4 T cells into Th17, Th1, or Treg cells and did not affect the proliferation and migration of human colon epithelial cells. In summary, HHT attenuates DSS-induced colitis by inhibiting macrophage-associated NF-κB activation and M1 polarization, which could be an option for the treatment of ulcerative colitis.